Audio Description in Abstract Art: Using Metaphors From a Functional Perspective - García Vizcaíno, María José (Journal of Audiovisual Translation, 2023)
The aim of this article is to analyze the linguistic techniques used to develop the audio description (AD) for a multimedia video installation and to reflect critically upon creativity and “invisibility” of AD in abstract art. Considering AD as a type of intersemiotic translation, a functionalist approach to audio description (Mazur, 2020) was adopted as our theoretical framework. Taking into account that the main function of art is aesthetic (Eisner, 2022; Iseminger, 2004) and considering the main goals of the exhibition, we embarked in a challenging decision-making process to determine what linguistic and creative techniques to use our particular piece. Among those techniques, metaphors proved to be very effective tools. The results indicate that the main metaphors to describe abstract art were synesthesia, participation, and vocal emphasis metaphors. Another conclusion is related to the degree of creativity in audio describing abstract art and the boundaries that the audio describer can easily trespass by creating metaphors that go beyond the source domain of the original work. It is precisely here where the function of the art piece and the purpose of the exhibition play a crucial role in finding that balance between fidelity and creativity. Lay summary This article analyses the linguistic techniques used to create audio description —the translation of images into words mainly intended for blind audiences— for a multimedia video installation in an art museum. Taking into account that the main function of art is aesthetic (Iseminger, 2004) and considering the main goals of the exhibition, we embarked on a challenging decision-making process to determine what linguistic and creative techniques to use for our particular piece. Among those techniques, metaphors proved to be very effective tools (Luque Colmenero & Soler Gallego, 2020). The results indicate that the main metaphors to describe abstract art were synaesthesia —incorporation of sensations experienced by senses such as touch, smell or hearing—, and vocal emphasis. Another conclusion is related to the degree of creativity in audio describing abstract art and the boundaries that the audio describer can easily trespass by crafting metaphors that go beyond the original work. It is precisely here where the function of the art piece and the purpose of the exhibition play a crucial role in finding that balance between fidelity and creativity.